2011
DOI: 10.1177/1479164111421804
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical predictors of increased carotid intima-media thickness in overweight and obese adolescents with type 2 diabetes

Abstract: CIMT is increased in adolescents with type 2 diabetes. Poor glycemic control, HOMA, increased C-reactive protein, body mass index, duration of diabetes, and elevated blood pressure are associated with early atherosclerosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Our study showed significant strong positive correlation between CIMT and CRP level among group I and group II with P <0.001. These reslts coincide with kotb et al [11] who stated that CIMT were significantly greater in adolescents with T2DM than in healthy subjects and correlated positively with C-reactive protein. They showed a significant elevation of hypersensitive C-reactive protein in uncontrolled than in controlled diabetic patients and this correlated positively with CIMT.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study showed significant strong positive correlation between CIMT and CRP level among group I and group II with P <0.001. These reslts coincide with kotb et al [11] who stated that CIMT were significantly greater in adolescents with T2DM than in healthy subjects and correlated positively with C-reactive protein. They showed a significant elevation of hypersensitive C-reactive protein in uncontrolled than in controlled diabetic patients and this correlated positively with CIMT.…”
Section: Discussionsupporting
confidence: 68%
“…Patients with T2DM have a two to fourfold increased incidence of CVD compared to persons without diabetes, which is also reflected by an increased CIMT in T2DM patients [1]. Kotb et al [11] found that CIMT was higher in diabetic patients than in healthy subjects. CIMT, HbA1C, systolic blood pressure, triglycerides, HOMA, and C-reactive protein were significantly higher in patients with uncontrolled than with controlled diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…250 Urbina et al 251 found that arterial stiffness, as measured by brachial artery distensibility and pulse-wave velocity, was associated with HOMA (homeostasis model assessment)-assessed IR in adolescents and young adults with T2DM, although not independently of age, sex, BMI, and BP. Similarly, Kotb et al 103 found that cIMT was higher in adolescents with T2DM than in control subjects and correlated with HOMA-assessed IR. Nadeau et al 250 reported reduced cardiopulmonary fitness in adolescents with T2DM compared with lean and obese adolescents, and this reduction in V .…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…[93][94][95][96][97] Factors associated with this higher cIMT include lower vitamin C levels 98 and longer duration of disease. 99,100 Adolescents with T2DM also demonstrate higher cIMT compared with healthy control subjects, 101,102 with diabetes mellitus duration 103 and glucose control playing a role. 104 Factors affecting the progression of cIMT in adolescents and young adults with diabetes mellitus include the number of receptors for advanced glycation end products, 105 HbA 1c , 106 and diabetes mellitus duration.…”
mentioning
confidence: 99%
“…The increase in the thickness of the carotid intima-media, measured by high-resolution ultrasonography, has been directly associated with atherosclerosis, myocardial infarction and stroke, high-resolution B-mode ultrasonography provides a noninvasive method that can detect an increase in arterial wall thickness [6]. …”
mentioning
confidence: 99%